Wear-resistant anti-fouling transparent glass ceramic device and preparation method thereof

By plating anti-fouling layer, carbon film layer and interface layer on the surface of chemically strengthened microcrystalline glass, the problem of insufficient anti-fouling and scratch resistance on the surface of consumer electronic equipment and vehicle-mounted display equipment is solved, and high wear resistance is achieved and anti-fouling properties extend the service life of the equipment.

CN119241086AInactive Publication Date: 2025-01-03深圳市昊迦科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411384277.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve stain resistance and scratch resistance on the surfaces of consumer electronic equipment and vehicle-mounted display equipment, resulting in stains and scratch damage on the glass surface.

Method used

Using chemically strengthened microcrystalline glass and plating functional layers on its surface, including anti-fouling layer, carbon film layer and interface layer, to optimize the composition and thickness of these layers to improve the Mohs hardness and dynamic friction coefficient of the surface and enhance the anti-fouling properties. and wear resistance.

Benefits of technology

It achieves high wear resistance and stain resistance of the surface of microcrystalline glass, and can be kept clean and intact under high-frequency use and collision friction conditions, significantly improving service life and user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241086A_ABST
    Figure CN119241086A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant and stain-resistant transparent microcrystalline glass device and a preparation method thereof. The wear-resistant and stain-resistant transparent microcrystalline glass device comprises a chemical reinforced microcrystalline glass body and a functional layer arranged on the surface of the chemical reinforced microcrystalline glass body, the functional layer sequentially comprises an anti-fouling layer, a carbon film layer and an interface layer from outside to inside; the surface Mohs hardness of the wear-resistant anti-fouling transparent glass ceramic device is greater than or equal to 6, the dynamic friction coefficient is less than or equal to 0.08, and the initial water drop angle is greater than or equal to 110 degrees. When the glass ceramic is applied to screens of consumer electronics and vehicle-mounted display equipment, the wear resistance and pollution resistance of the surface of a glass ceramic device can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass preparation, and in particular to a wear-resistant and anti-fouling transparent microcrystalline glass device and a preparation method thereof. Background Art

[0002] In some frequently used human-computer interaction interfaces, such as touch screen surfaces of consumer products such as mobile phones, tablet computers, smart wearable devices, and surfaces of in-vehicle smart devices, as the frequency and time of use increase, sweat, dust, oil and other dirt will adhere to the glass surface. Users will obviously feel that the human-computer interaction interface is blocked, making it inconvenient to use.

[0003] At the same time, due to the diverse usage scenarios of the above-mentioned electronic products, the frequency and time of use are very high, and the surface of devices with glass as protective screen materials will often collide and rub against other hard objects, causing scratches or even damage to the human-computer interaction interface.

[0004] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a wear-resistant and anti-fouling transparent microcrystalline glass device and a preparation method thereof, aiming to meet the scratch resistance and anti-fouling requirements required for the surface of existing consumer electronic devices or vehicle-mounted display devices.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In a first aspect, a wear-resistant and anti-fouling transparent microcrystalline glass device comprises: a chemically strengthened microcrystalline glass body and a functional layer arranged on the surface of the chemically strengthened microcrystalline glass body; the functional layer comprises an anti-fouling layer, a carbon film layer and an interface layer in sequence from the outside to the inside;

[0008] The surface Mohs hardness of the wear-resistant and anti-fouling transparent microcrystalline glass device is ≥6, the dynamic friction coefficient is ≤0.08, and the initial water drop angle is ≥110°.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the average crystallinity of the chemically strengthened microcrystalline glass body is ≥50%, and SiO 2 The glass phase accounts for 40wt% to 50wt%.

[0011] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the chemically strengthened microcrystalline glass comprises the following components in molar percentage:

[0012] SiO 2 :35%~60%;

[0013] A l 2 O 3 :8%~22%;

[0014] Na 2 O: 10%~25%;

[0015] Li 2 O: 1%~9%;

[0016] K 2 O: 0%~1%;

[0017] MgO: 0~3%;

[0018] ZrO 2 :0.5%~3.5%;

[0019] B 2 O 3 :0%~3%;

[0020] CaO: 0%~2%;

[0021] P 2 O 5 :0.5%~3%;

[0022] T i 2 :0~0.5%;

[0023] SnO 2 :0~0.3%.

[0024] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the crystal phase of the chemically strengthened microcrystalline glass body includes: one or more of sodium nepheline, triclinic nepheline, zirconium oxide and β-quartz solid solution.

[0025] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the interface layer is a compound containing a silicon-oxygen bond or a mixed silicon oxide, the thickness of the interface layer is recorded as T1, 1nm≤T1≤30nm; the carbon film layer is a polymer carbon layer with a molecular weight greater than 5000; the thickness of the carbon film layer is recorded as T2, 50nm≤T2≤100nm,

[0026] The anti-fouling layer is a fluorine-containing polyether silicon oxide layer with a molecular weight of not less than 2000, and the thickness of the anti-fouling layer is T3, T3≥30nm; and 100nm≤T1+T2+T3≤300nm.

[0027] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the surface of the wear-resistant and anti-fouling transparent microcrystalline glass device can withstand steel wool friction times ≥15,000 times under a force of 750g; and can withstand eraser friction times ≥3,000 times.

[0028] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the wear-resistant and anti-fouling transparent microcrystalline glass device has a transmittance Tr ≥ 90% and a haze Haze ≤ 0.15 at a wavelength of 360-740nm when the thickness is ≤ 1.0mm; and the color control LAB value |B| ≤ 1.2.

[0029] As a preferred technical solution, the wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the surface shape of the wear-resistant and anti-fouling transparent microcrystalline glass device is one of 2D, 2.5D or 3D forms.

[0030] In a second aspect, a method for preparing the wear-resistant and anti-fouling transparent microcrystalline glass device according to the first aspect, comprising:

[0031] Providing the chemically strengthened glass-ceramic body;

[0032] The interface layer, the carbon film layer and the anti-fouling layer are sequentially prepared on the surface of the chemically strengthened microcrystalline glass body to obtain the wear-resistant and anti-fouling transparent microcrystalline glass device.

[0033] In a third aspect, an electronic device includes: a wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the wear-resistant and anti-fouling transparent microcrystalline glass device is the wear-resistant and anti-fouling transparent microcrystalline glass device described above.

[0034] Beneficial effects: Compared with the prior art, the present invention, by coating a functional layer on the surface of chemically strengthened microcrystalline glass, makes its Mohs hardness not less than 6, and at the same time, the dynamic friction coefficient of the surface of the microcrystalline glass device is ≤0.08, and the initial water drop angle is ≥110°. When it is used in consumer electronic products and vehicle-mounted display screens, it can greatly improve the wear resistance and anti-fouling properties of the surface of the microcrystalline glass device. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the structure of a wear-resistant and anti-fouling transparent micro-ceramic glass device provided in an embodiment of the present invention;

[0036] Figure 2 This is a comparison of the coated and uncoated areas on the surface of the wear-resistant and anti-fouling transparent micro-ceramic glass device after 3000 eraser tests;

[0037] Figure 3 This is a comparison of the surface of a glass-ceramic device magnified 5000 times and 18000 times after it was rubbed with steel wool 15000 times;

[0038] Figure 4 This is a graph showing the transmittance of the wear-resistant and anti-fouling transparent micro-glass device to light in the wavelength range of 360nm to 740nm;

[0039] Figure 5 This is a test diagram of the water drop angle of the microcrystalline glass device. DETAILED DESCRIPTION

[0040] The present invention provides a wear-resistant and anti-fouling transparent microcrystalline glass device and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and do not mean a necessary sequence, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., assigned to the components herein are only used to distinguish the objects described and do not have any order or technical meaning.

[0042] Terminology explanation:

[0043] Basic glass: refers to glass that has not been treated with nucleation, crystallization or strengthening.

[0044] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and microcrystalline phase / crystalline phase and is prepared by targeted controlled crystallization of substrate glass. The microcrystalline phase here is also called crystalline phase or crystal phase in other literature.

[0045] Chemically strengthened glass-ceramics: It is a solid composite material obtained after chemical strengthening treatment of glass-ceramics. It should be understood that during high-temperature chemical strengthening treatment, alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt / molten salt will replace alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the glass-ceramics, thereby generating an exchange ion volume difference and generating compressive stress on the surface of the glass-ceramics.

[0046] Total crystalline phase content: the percentage of the mass of the crystalline phase in the microcrystalline glass to the total mass of the microcrystalline glass.

[0047] Color control LAB value b value: used to characterize the yellow-blue value of microcrystalline glass materials. The optical b value in the present invention is the transmitted light b value, and a positive optical b value indicates that the material is blue.

[0048] 2D, 2.5D, 3D: 2D design usually refers to design on a plane, that is, using width and height to indicate the position and shape of elements. 2.5D design is a transitional form between 2D and 3D. It simulates 3D effects on a plane, giving people a three-dimensional feeling. By adding layers, shadows, perspective and other techniques, the flat elements present a certain three-dimensional sense. 3D design uses three dimensions, namely width, height and depth, to indicate the position and shape of elements. It uses perspective, projection, light and shadow and other techniques to present a three-dimensional sense in the design.

[0049] Mohs hardness: also known as Mohs hardness, is a standard for indicating the hardness of minerals. Mohs hardness is not an absolute hardness value, but a value expressed in the order of hardness. Mohs hardness is a relative hardness expressed by the scratches on the surface of the tested mineral using the scratch method (scratch method). The scratches are divided into ten levels to indicate the hardness. The hardness of the tested mineral is determined by comparing it with ten reference minerals. If a reference mineral can scratch the tested mineral, it means that the Mohs hardness is less than that of the reference mineral. If it cannot scratch, it means that the Mohs hardness is greater than that of the reference mineral.

[0050] Mohs Hardness Scale

[0051]

[0052] Dynamic friction coefficient: Dynamic friction coefficient is also called dynamic friction factor. It is represented by the Greek letter μ in physics. This value is the ratio between the sliding friction force and the normal pressure when two objects in contact with each other move relative to each other. The dynamic friction coefficient between objects of different materials is different. The rougher the object, the greater the dynamic friction coefficient.

[0053] Water drop angle: The water drop angle is defined as the angle between the gas-liquid interface and the solid-liquid interface at the interface of solid, liquid and gas. The water drop angle is a measure of the humidity on the solid surface. It is measured using most of the droplets of solid matter. A low contact angle indicates that the surface is high in humidity (hydrophilic) and easy to stick to. A high contact water drop angle indicates that the surface is hydrophobic, the surface is heavily organically contaminated or the surface adhesion is poor. The contact angle of a liquid in contact with a flat solid surface is measured by the end point of the water drop curve at the liquid-solid-gas junction and the contact point on the solid surface to analyze the surface cleanliness. The contact angle is a measure of the humidity on the solid surface. It is measured using most of the droplets of solid matter. A low contact angle indicates that the humidity is high (hydrophilic, hydrophobic) and the surface energy is low.

[0054] Smoothness: In flexographic printing, the degree of fineness of the printed surface is called smoothness. Due to the lack of corresponding testing instruments, quantitative description is very difficult; operators often judge whether the smoothness meets the requirements by feel.

[0055] The inventors have found that the scratch resistance and stain resistance of ordinary glass can be increased by spraying or electroplating a layer of PFPE (perfluoropolyether, a type of fluorinated polyether silicon oxide) on the glass surface. The structure of the fluorinated polyether silicon oxide (such as alkoxy silicide) is as follows:

[0056]

[0057] Among them, R can be carbon, hydrogen or silicon; Y can be an ether bond, sulfur-containing hydrocarbon group, sulfur-containing alkoxy group, nitrogen-containing hydrocarbon group, nitrogen-containing alkoxy group, epoxyalkyl group, acyloxyalkyl group, hydrocarbon group, sulfide group, etc. The process of connecting PFPE to glass is a chemical reaction process. PFPE is hydrolyzed (PFPE-Si-OR+H2O->PFPE-Si-OH+ROH), and then dehydration condensation reaction (such as PFPE-Si-OH+HO-Si→H2O+PFPE-Si-O-Si-), and finally the PFPE film is connected to the SiO structure on the glass interface by valence bond.

[0058] Since ordinary glass contains a large amount of SiO structures, PFPE has the conditions to directly react with glass to form a film. 2 The mass ratio is usually close to 70%, and in glass-ceramics, part of Si participates in the formation of nanocrystals, and in glass-ceramics with a crystallinity of ≥50%, the remaining SiO 2 The mass ratio of the glass phase is between 40wt% and 50wt%, SiO 2 The mass of the film is only half of that of ordinary glass. The adhesion of the film produced by the chemical reaction process between the above-mentioned PFPE and microcrystalline glass is not high and the adhesion is insufficient.

[0059] In order to solve the above technical problems, the inventors of the present application adopted a process of coating the surface of chemically strengthened microcrystalline glass to prepare a functional layer to improve its anti-fouling and wear-resistant properties. Specifically, Figure 1As shown, the wear-resistant and anti-fouling transparent microcrystalline glass device provided by the present invention comprises: a chemically strengthened microcrystalline glass body 10 and a functional layer 20 arranged on the surface of the chemically strengthened microcrystalline glass body; the functional layer 20 comprises an anti-fouling layer 21, a carbon film layer 22 and an interface layer 23 from the outside to the inside; the surface Mohs hardness of the wear-resistant and anti-fouling transparent microcrystalline glass device is ≥6, the dynamic friction coefficient is ≤0.08, and the initial water drop angle is ≥110°. It should be noted that the coating process used is a conventional process in the prior art and is not limited here.

[0060] In the present invention, the interface layer is a compound containing Si-O bonds or a mixed silicon oxide layer, and the thickness of the base layer is T1, satisfying 1nm≤T1≤30nm; the thickness of the interface layer can be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc. and any value in the range composed of any two of the above values.

[0061] The carbon film layer is a natural diamond-like carbon film layer, which is a polymer carbon layer with a molecular weight greater than 5000; the thickness of the carbon film layer is measured as T2, satisfying 50nm≤T2≤100nm. The natural diamond-like layer is one of the key materials in the present invention that enables the microcrystalline glass device to have a Mohs hardness ≥6. The main material of the film layer is a polymer carbon layer with a molecular weight greater than 5000 formed by bombarding a graphite target. The larger the molecular weight, the better its wear resistance, and the thicker the thickness, the better its wear resistance. However, since the coating process is about 10nm-20nm thick each time, multiple coatings are required to achieve a thicker film layer. The thickness error of each coating process is required to be small to obtain excellent optical properties. At the same time, the film thickness also needs to be controlled between a certain thickness. The thickness of the diamond-like carbon film layer in the microcrystalline glass device in the present invention is between 50nm and 100nm, and can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, and any value in the range composed of any two of the above values.

[0062] The anti-fouling layer T3 is a fluorine-containing polyether silicon oxide layer with a molecular weight of not less than 2000. The thickness of the anti-fouling layer is calculated as T3, satisfying T3≥30nm; the anti-fouling layer is mainly the layer that contacts the user of the microcrystalline glass device. The larger the molecular weight of the fluorine polyether silicon oxide, the better the anti-fouling effect. The test shows that the higher the initial water drop angle, the higher the remaining water drop angle after multiple steel wool frictions. In order to ensure that the water drop angle on the surface of the microcrystalline glass device is ≥100° after ≥15,000 steel wool frictions, the thickness of the anti-fouling layer on the surface of the microcrystalline glass device in the present invention is ≥30nm.

[0063] The total thickness of the above-mentioned interface layer T1+natural diamond-like carbon film layer T2+anti-fouling layer T3 needs to be controlled within a certain range to ensure that the microcrystalline glass device has both excellent wear resistance and excellent optical performance, and meets the optical performance requirements of consumer electronic products and vehicle-mounted display devices. In the present invention, T1, T2, and T3 satisfy the relationship of 100nm≤T1+T2+T3≤300nm. For example, it can be 100nm, 150nm, 200nm, 250nm, 300nm, and any value in the range of any two of the above values.

[0064] In some embodiments of the present invention, the transparent super-hard coated anti-fouling microcrystalline glass device has excellent optical properties. When the thickness is ≤1.0mm, at the wavelength of 360-740nm, the transmittance Tr is ≥90%, and the haze Haze is ≤0.15; the color control LAB value |B| is ≤1.2.

[0065] In the present invention, the chemically strengthened microcrystalline glass body comprises the following components, measured in molar percentage: SiO 2 :35%~60%;Al 2 O 3 :8%~22%;Na 2 O: 10%~25%; Li 2 O: 1%~9%; K 2 O:0%~1%; MgO:0~3%; ZrO 2 :0.5%~3.5%; B 2 O 3 :0%~3%; CaO:0%~2%; P 2 O 5 :0.5%~3%; TiO 2 :0~0.5%; SnO 2 :0~0.3%. Among them, SiO 2 As one of the main components of the network oxide of basic glass and microcrystalline glass, it is one of the important components that compose the Si-O tetrahedron in the main body and form the network structure.

[0066] Al 2 O 3 It is an intermediate oxide in the formation of glass, which can significantly improve the thermal stability of base glass and glass-ceramics. 4 ] than [SiO 4 ] has a large volume, which can provide more space for ion exchange, so alumina can promote ion exchange. 2 O 3 It will increase the viscosity of the glass and is not conducive to melting.

[0067] Na 2O is an important element in glass-ceramics that participates in ion exchange chemical strengthening to obtain tempered glass-ceramics. It is also a flux for high-temperature melting of base glass, which can significantly reduce the melting temperature of base glass. However, when Na 2 When the O content is higher than 25wt%, the chemical stability of the glass-ceramics is significantly reduced. 2 The mass fraction of O is less than or equal to 25.0wt%. At this time, the melting temperature can be kept within a suitable range and good ion exchange properties can be ensured.

[0068] K 2 O can reduce the high temperature viscosity of the base glass, significantly improve the formability and fluidity of the base glass at high temperature, and significantly reduce the incidence of cracks. Among them, a small amount of K2O can slow down the crystallization behavior during the molding of microcrystalline glass.

[0069] Li 2 O is an oxide with high activity of alkali metals and an external oxide of the glass network. As one of the additives for reducing the high-temperature viscosity of the base glass, it can significantly improve the high-temperature fluidity of the base glass. At the same time, Li+ in the microcrystalline glass provided by the present invention can participate in the ion exchange chemical strengthening reaction to further enhance the mechanical properties of the microcrystalline glass.

[0070] The crystal nucleating agent is preferably TiO 2 and / or ZrO 2 and or P 2 O 5 , TiO 2 、ZrO 2 and P 2 O 5 All of them can be used as nucleating agents alone or in combination of two or three to improve the crystallization ability of microcrystalline glass, so that a large number of uniform and fine crystals can be produced in a relatively short time of microcrystallization treatment.

[0071] MgO is preferably 0.00% to 3.00%. As a component of some basic glasses, magnesium oxide can improve the microcrystallization ability of the crystal by adding it to a certain extent. Magnesium oxide can also reduce the difficulty of melting and increase the hardness of the glass.

[0072] CaO, as a network-forming oxide, helps reduce the viscosity of glass, inhibits glass crystallization during glass forming, and improves the low-temperature melting property of glass. However, excessive CaO will reduce the devitrification resistance of glass. By adding an appropriate amount of CaO, the viscosity of glass can be reduced without affecting the crystallization performance of glass.

[0073] B 2 O 3As a network oxide of glass, it is generally filled in the gaps of the silicon-oxygen tetrahedral framework. Its cation coordination rarely changes, and some properties of its oxide can be considered constant. B2O3 helps to provide a basic glass with a low melting temperature. In addition, adding B2O3 to the basic glass 2 O 3 , and can also improve the damage resistance of microcrystalline glass.

[0074] It should be understood that in the present invention, the composition of the base glass is the same as that of the transparent glass-ceramics in terms of the molar percentage of oxides. The forming methods of the base glass include but are not limited to float, overflow, rolling and continuous melting casting.

[0075] In some embodiments of the present invention, when preparing the base glass, a clarifier may be added to the base glass. In the present invention, SnO 2 As a clarifier; based on the mass of the substrate glass, the amount of the clarifier added is 0.00 mol% to 0.30 mol%, preferably 0.01 mol% to 0.20 mol%.

[0076] In some embodiments of the present invention, the main crystal phase in the glass body of the wear-resistant and anti-fouling transparent microcrystalline glass device includes triclinic nepheline, sodium nepheline, β-quartz solid solution or ZrO 2 One or more of;

[0077] The surface of the microcrystalline glass device can withstand steel wool friction for ≥15,000 times and eraser friction for ≥3,000 times under a force of 750g.

[0078] It should be noted that in the present invention, when testing the crystalline phase content of the glass body of the microcrystalline glass device, the microcrystalline glass is first ground into a fine powder, and then the XRD diffraction data of the fine powder is obtained by testing, and then the XRD diffraction data is fitted and calculated by the analysis software to obtain the crystalline phase content of the microcrystalline glass. The above-mentioned analysis software may include but is not limited to Gsas, Fullprof, Maud, Jade, etc.

[0079] The specific test method is as follows:

[0080] 1. Water drop angle test: Use a water drop angle tester to drop 2.5UL pure water on the surface of the object to be tested, and test 9 points at the top, middle and bottom of each piece. Test the water drop angle before coating, and test the initial water drop angle after coating. When passing the steel wool test, test the water drop angle again after rubbing 2000 times, and measure 10 samples to get the average value.

[0081] 2. Eraser test: Minoan eraser, load 1kg, speed 40 cycles / min, stroke 40mm, measure 15,000 times at the same position, divided into 5 sections, excluding the upper and lower sections, measure the water drop angles of the upper, middle and lower sections. Measure 10 samples every 1,000 times and take the average value. The test environment temperature is (23±2)℃, and the relative humidity is (70±10)%.

[0082] 3. Steel wool friction test: Use 1CMX1CM steel wool, load 1kg, speed 40cyc l es / min, stroke 40mm, measure 15000 times at the same position, measure 10 samples and take the average value. The test environment temperature is (23±2)℃, and the relative humidity is (70±10)%.

[0083] 4. Mohs hardness test: Use Mohs hardness pen with a load of 750g, the pen is tilted at 45°, the tip is pointed left, the speed is 40, the stroke is 40mm, and 3 lines are tested (after cleaning the surface, visually inspect under fluorescent light). Measure 10 samples and take the average value.

[0084] 5. Test of optical properties (1) A microcrystalline glass polished sheet with a length, width and thickness of 50 mm × 50 mm × 0.64 mm was cleaned in an ultrasonic cleaning machine. The cleaning conditions are as follows: the cleaning time is 5 min, the cleaning agent used is deionized water, the cleaning temperature is 50°C, and the cleaning frequency is 40 KHz. (2) After cleaning, the test is performed with reference to the test method of the national standard GB / T 7962.12-2010 "Test method for colorless optical glass Part 12: spectral transmittance", and the transmittance and optical b value of the microcrystalline glass polished sheet are tested using a haze meter. The haze meter used in the present invention is a Japanese Konica Minolta spectrophotometer CM-3600A, the light receiving optical system is transmission, the spectral mode is a diffraction grating, the wavelength range is 360nm to 740nm, the wavelength spacing is 10nm, the illumination light source is a pulsed xenon lamp X4, the ambient temperature of the instrument is 24°C, and the air humidity is 40%.

[0085] 7. Crystal phase test: The microcrystalline glass sheet is ground into glass fine powder with a grinding machine, and the maximum size of the fine powder particles is less than 75μm. Then, an X-ray diffractometer (Shimadzu XRD-6100) is used to test it under the conditions of a diffraction angle range of 2θ=10°-80°, a scanning speed of 10° / min, a working voltage of 40kV, and a working current of 30mA to obtain an XRD diffraction peak curve. The XRD diffraction data is then analyzed using the professional processing software Jade, and the crystal phase contained in the microcrystalline glass is analyzed. At the same time, the glass diffraction peak curve is fitted to obtain the total crystal phase content in the microcrystalline glass. Specifically, the method for obtaining the crystal phase content is as follows: the X-ray diffractometer test result file (RAW format) is imported into the X-ray diffraction data Rietveld refinement software Jade, and the total crystal phase content in the microcrystalline glass is obtained by fitting and calculating. The ratio of the fitted crystal phase peak area to the fitted total peak area is the total crystal phase content, also known as crystallinity.

[0086] In the above test method, after the wear-resistant and anti-fouling transparent microcrystalline glass devices are shaped, cut and polished, microcrystalline glass samples (microcrystalline glass polished sheets) of the desired size can be obtained, and then tested, such as microcrystalline glass polished sheets with a length, width and thickness of 50mm×50mm×0.7mm, 10mm×10mm×1.0mm and 50mm×50mm×0.64mm.

[0087] 8. Film thickness test: Use optical measurement method to test the coating thickness online, integrate the film thickness test device into the coating machine, and install the film thickness test module in the coating control software when coating the microcrystalline glass device. Measure the thickness of each layer of coating online. The principle is to control the film thickness by real-time monitoring of optical interference or transmittance changes. As the thickness of the film increases, the phase difference of light or the intensity of transmitted light will change periodically, and the thickness of the film is determined based on these changes. Some embodiments of the present invention measure the film thickness of at least 10 samples and take the average value. In the present invention, a micrometer is used to test the thickness of transparent microcrystalline glass.

[0088] Based on the same inventive concept, the present invention also provides a method for preparing a wear-resistant and anti-fouling transparent microcrystalline glass device, comprising:

[0089] S10, providing the chemically strengthened glass-ceramics body.

[0090] Specifically, according to SiO 2 :35%~60%; A l 2 O 3 :8%~22%;Na 2 O: 10%~25%; Li 2 O: 1%~9%; K 2O:0%~1%; MgO:0~3%; ZrO 2 :0.5%~3.5%; B 2 O 3 :0%~3%; CaO:0%~2%; P 2 O 5 :0.5%~3%; TiO 2 :0~0.5%; SnO 2 : 0~0.3%, weigh all raw materials and mix them evenly, melt them at 1580℃, and adopt one of the molding methods such as overflow method, float method, roller pressing method or casting method to obtain basic glass; subject the basic glass to nucleation and crystallization heat treatment to obtain microcrystalline glass body; the microcrystalline glass is subjected to deep processing steps such as cutting, grinding and polishing, ion exchange chemical strengthening, etc. to obtain transparent chemically strengthened microcrystalline glass.

[0091] S20, sequentially preparing the interface layer, the carbon film layer and the anti-fouling layer on the surface of the chemically strengthened microcrystalline glass body to obtain the wear-resistant, anti-fouling, transparent microcrystalline glass device.

[0092] Among them, the preparation method of the coating layer in this application is as follows:

[0093] Preparation of interface layer: spray or electroplate a layer of compound containing silicon-oxygen bond or mixed silicon oxide on the surface of chemically strengthened microcrystalline glass, the thickness of the interface layer is T1, the thickness is 1nm≤T1≤30nm, and the coating method is preferably electroplating; electroplating is performed twice, each time with a thickness of about 5nm. That is, the thickness of the interface layer in this application is preferably 10nm.

[0094] Preparation of natural diamond-like carbon film: A polymer carbon layer with a molecular weight greater than 5000 is deposited on the interface layer by magnetron sputtering, and the thickness of the carbon film is T2, 50nm≤T2≤100nm. In the present application, the thickness of the natural diamond-like carbon film is preferably 70nm.

[0095] Preparation of anti-fouling layer: by spraying or electroplating a layer of fluorinated polyether silicon oxide with a molecular weight of not less than 2000 on the surface of the natural diamond-like carbon film layer, the thickness of the anti-fouling layer is T3, T3≥30nm; in this application, the anti-fouling layer is preferably electroplated, and the coating thickness is preferably 40nm.

[0096] Furthermore, the total thickness of the three layers is in the range of 100nm≤T1+T2+T3≤300nm.

[0097] In addition, the strengthened microcrystalline glass coating can be a continuous coating, that is, the production equipment of the interface layer, the carbon film layer and the anti-fouling layer are combined into an assembly line equipment, and the entire production line is closed in an environment with a higher purification level (such as a hundred-level or thousand-level environment), that is, after the same film layer of a batch of strengthened microcrystalline glass is completed, it automatically moves to the next film layer through a transmission device, and UV ultraviolet irradiation equipment is added in the middle to quickly solidify the coating until the above three layers of coating are completed; it can also be a single-layer coating, that is, a coating cavity is set for each coating process, and a microcrystalline glass fixture is set inside. The number of microcrystalline glasses is put in according to the cavity capacity and the size of the fixture. After the corresponding film layer is completed, UV ultraviolet irradiation is used to accelerate the curing of the film layer or let it stand for a period of time to allow the coating to react completely, and then the microcrystalline glass is moved to the next coating cavity for the next film layer operation. Monomer coating is preferred in this application.

[0098] Specifically, the transparent chemically strengthened microcrystalline glass is subjected to the coating processes of an interface layer, a natural diamond-like carbon film layer, and an anti-fouling layer to obtain the transparent super-hard coated anti-fouling microcrystalline glass device.

[0099] In some implementation cases of the present invention, a transparent super-hard coated anti-fouling microcrystalline glass device, having a surface shape of 2D, 2.5D or 3D, can be used as a protective cover glass material for consumer electronic devices and vehicle-mounted display devices, wherein the electronic devices include at least one of mobile phones, tablet computers, smart wearables, monitors and televisions.

[0100] The above technical solution provided by the present invention is further explained below through specific embodiments.

[0101] Table 1 Material formula

[0102]

[0103]

[0104] Table 2

[0105]

[0106] Table 2 shows the optical performance parameters of the microcrystalline glass corresponding to Examples A1-9 after heat treatment and chemical strengthening of Examples 1-9.

[0107] Table 3 Rubber friction test under the same coating conditions

[0108]

[0109]

[0110] Table 3 shows the glass-ceramics of Examples B1-9 after the same coating treatment as Examples A1-A9.

[0111] Table 4 Steel wool friction test under the same coating conditions

[0112]

[0113] Table 4 shows the steel wool friction test data of a portion randomly selected from the above embodiments B1-B9 under the same coating conditions.

[0114] Table 5 Test performance under different coating conditions

[0115]

[0116]

[0117] Table 5 shows that Examples C1-9 are microcrystalline glasses after Examples A1-A9 have been treated with different coatings. The carbon film layer of Example C6 is thin, resulting in a Mohs hardness lower than 6, and the steel wool friction resistance and rubber friction resistance times do not meet the requirements. At the same time, the smoothness after friction is rough. In Example C8, the anti-fouling layer thickness is 100nm, resulting in a slightly lower Mohs hardness. In addition, the anti-fouling layer in C9 is slightly thin, and its anti-fouling effect is not very good. Overall, the carbon film layer is closely related to the hardness, and the thicker the carbon film layer, the higher the hardness. However, it is necessary to ensure that the overall thickness of the coating layer is within the range of 100-300nm, otherwise it may affect its optical properties.

[0118] The embodiments of the present invention obtain the base glass by casting or rolling, so the thickness of the base layer needs to be controlled within the range of 1-30nm. If the thickness of the base layer is higher than 30nm, the van der Waals force between the microcrystalline glass body and the base layer will be reduced, resulting in a decrease in the adhesion of the coating layer, which ultimately affects the mechanical properties. For example, the thickness of the base layer in Example C7 is reduced, and the thickness of the base layer is greater than 30nm, so the resistance to steel wool friction and rubber friction is reduced, and the surface is rough.

[0119] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A wear-resistant and anti-fouling transparent microcrystalline glass device, characterized in that: include: A chemically strengthened glass-ceramics body and a functional layer arranged on the surface of the chemically strengthened glass-ceramics body; the functional layer comprises an anti-fouling layer, a carbon film layer and an interface layer in sequence from the outside to the inside; The surface Mohs hardness of the wear-resistant and anti-fouling transparent microcrystalline glass device is ≥6, the dynamic friction coefficient is ≤0.08, and the initial water drop angle is ≥110°.

2. The wear-resistant and anti-fouling transparent micro-ceramic glass device according to claim 1, characterized in that: The average crystallinity of the chemically strengthened microcrystalline glass body is ≥50%, and the proportion of SiO2 in the remaining glass phase is between 40wt% and 50wt%.

3. The wear-resistant and anti-fouling transparent micro-ceramic glass device according to claim 1, characterized in that: The chemically strengthened glass-ceramic body comprises the following components in molar percentage: SiO2: 35%~60%; Al2O3: 8%~22%; Na2O: 10%~25%; Li2O: 1%~9%; K2O: 0%~1%; MgO: 0~3%; ZrO2: 0.5%~3.5%; B2O3: 0%~3%; CaO: 0%~2%; P2O5: 0.5%~3%; TiO2: 0~0.5%; SnO2: 0~0.3%.

4. The wear-resistant and anti-fouling transparent micro-ceramic glass device according to claim 1, characterized in that: The crystalline phase of the chemically strengthened microcrystalline glass body includes one or more of sodium nepheline, triclinic nepheline, zirconium oxide and beta quartz solid solution.

5. The wear-resistant and anti-fouling transparent microcrystalline glass device according to any one of claims 1 to 4, characterized in that: The interface layer is a compound containing silicon-oxygen bonds or a mixed silicon oxide, and the thickness of the interface layer is recorded as T1, 1nm≤T1≤30nm; the carbon film layer is a polymer carbon layer with a molecular weight greater than 5000; the thickness of the carbon film layer is recorded as T2, 50nm≤T2≤100nm, The anti-fouling layer is a fluorine-containing polyether silicon oxide layer with a molecular weight of not less than 2000, and the thickness of the anti-fouling layer is T3, T3≥30nm; and 100nm≤T1+T2+T3≤300nm.

6. The wear-resistant and anti-fouling transparent microcrystalline glass device according to claim 1, characterized in that: The surface of the wear-resistant and anti-fouling transparent microcrystalline glass device can withstand steel wool friction for ≥15,000 times under a force of 750g, and can withstand eraser friction for ≥3,000 times.

7. The wear-resistant and anti-fouling transparent microcrystalline glass device according to claim 1, characterized in that: When the wear-resistant and anti-fouling transparent microcrystalline glass device has a thickness of ≤1.0 mm, at a wavelength of 360-740 nm, a transmittance Tr ≥90%, and a haze Haze ≤0.15; and the color control LAB value |B| ≤1.

2.

8. The wear-resistant and anti-fouling transparent microcrystalline glass device according to claim 1, characterized in that: The surface shape of the wear-resistant and anti-fouling transparent microcrystalline glass device is one of 2D, 2.5D or 3D forms.

9. A method for preparing the wear-resistant and anti-fouling transparent microcrystalline glass device according to claim 1, characterized in that: include: Providing the chemically strengthened glass-ceramic body; The interface layer, the carbon film layer and the anti-fouling layer are sequentially prepared on the surface of the chemically strengthened microcrystalline glass body to obtain the wear-resistant and anti-fouling transparent microcrystalline glass device.

10. An electronic device, characterized in that: include: A wear-resistant and anti-fouling transparent microcrystalline glass device, wherein the wear-resistant and anti-fouling transparent microcrystalline glass device is the wear-resistant and anti-fouling transparent microcrystalline glass device according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Laminates with a polymeric scratch resistant layer

    CN105705473A

  • Microcrystalline glass device

    CN110550865A

  • Wear-resistant glass and preparation method thereof

    CN110922064A

  • Glass ceramic and preparation method thereof

    CN118598527A

  • Natryptite glass ceramic, chemically strengthened Natryptite glass ceramic and preparation method and application of chemically strengthened Natryptite glass ceramic

    CN118598528A